2018
DOI: 10.1101/355644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expanded genetic landscape of chronic obstructive pulmonary disease reveals heterogeneous cell type and phenotype associations

Abstract: SummaryChronic obstructive pulmonary disease (COPD) is the leading cause of respiratory mortality worldwide. Genetic risk loci provide novel insights into disease pathogenesis. To broaden COPD genetic risk loci discovery and identify cell type and phenotype associations we performed a genome-wide association study in 35,735 cases and 222,076 controls from the UK Biobank and additional studies from the International COPD Genetics Consortium. We identified 82 loci with P value < 5×10−8; 47 were previously des… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 108 publications
(128 reference statements)
0
54
0
Order By: Relevance
“…Nevertheless, we were able to reproduce some of the top SNP-smoking interactions in the CHARGE consortium 53 at nominal significant level. More importantly, our study identified 3 loci 2q37.3, 11p15.2-3 and 7p15.2-3 using a dataset of only 3,300 African-American individuals, while the same loci only passed the genome-wide significance threshold of standard univariate association in an independent replication cohort including up to 400,000 individuals 54,55 . Further, the method for admixture mapping can also be optimized.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Nevertheless, we were able to reproduce some of the top SNP-smoking interactions in the CHARGE consortium 53 at nominal significant level. More importantly, our study identified 3 loci 2q37.3, 11p15.2-3 and 7p15.2-3 using a dataset of only 3,300 African-American individuals, while the same loci only passed the genome-wide significance threshold of standard univariate association in an independent replication cohort including up to 400,000 individuals 54,55 . Further, the method for admixture mapping can also be optimized.…”
Section: Discussionmentioning
confidence: 76%
“…We considered two large studies of pulmonary phenotypes and COPD conducted in individuals of European ancestry: the CHARGE consortium (N = 50,047) which had genome-wide summary results for SNP-by-smoking interaction 53 ; and the most recent and largest meta-analysis of UK Biobank and SpiroMeta cohorts (COPD cases = 35,735, COPD controls = 222,076; N = 400,102 for pulmonary function phenotypes) which provides an up-to-date list of variants with genome-wide significant marginal genetic effect. 54,55 .…”
Section: Replication Of Association Signals In European Gwassmentioning
confidence: 99%
See 2 more Smart Citations
“…Machine learning techniques are one approach to discover enrichment of association of known genetic risk loci with a subgroup of COPD patients with shared clinical features [18]. The differential strength of association of COPD risk variants with COPD-related phenotypes, such as quantitative imaging features, can also be used to explore the genetic basis for COPD heterogeneity [9,19]. Aside from these techniques, studying the genetics of sub-phenotypes and key physiological features of respiratory diseases may allow us to more directly evaluate the biological processes contributing to the clinical and physiological heterogeneity of these diseases, and in particular, COPD.…”
mentioning
confidence: 99%